Coaching elite athletes: How coaches stimulate elite athletes' reflection - Hansen, P. O.; Andersen, S. S. (Sports Coaching Review, 2014)
This article investigates the coaching behaviour of five Norwegian national elite team coaches in cross-country skiing. It identifies how they acted as `sensegivers` towards the athletes. An important part of this is how coaches, assisted by support personnel, stimulated athletes' reflections in ways that improved the quality of everyday training. It draws upon social and relational aspects of learning within an organizational setting. The theory of mindful organizations, with its emphasis on sensemaking and sensegiving, is introduced to capture how coaches and support personnel can influence athletes' reflections. The article makes both an empirical and theoretical contribution. First, it directs attention to sensegiving as an important element of coaching behaviour. Second, it identifies key mechanisms of sensegiving not previously discussed in the literature.